Analysis of Deposit Calculations and Reporting Personal Income Tax Uses E-Form Application on Personal Wp Registered at Kpp Tegalaga - Muhtarudin Muhtarudin; Maisa Azizah Asmara; Rikky Wisnu Nugraha; Hamida Hamida; Rani Ahsani Alfi (Research Collaboration Community (RCC), 2023)
Personal income tax is a tax imposed on personal tax subjects on income received or earned in one tax year and has been regulated in Law no. 36 of 2008 concerning Income Tax. In this study using a qualitative descriptive method, namely collecting available data, compiling it, studying it, and then conducting further analysis regarding the calculation, deposit and reporting of Personal Income Tax on personal taxpayers registered at The Pratama Bandung Tegalega Tax Service Office. Based on the results of the analysis conducted, it can be concluded that the personal taxpayers registered at the Pratama Bandung Tegalega Tax Service Office as a whole have an average income of more than one source, where the tax calculation results in underpaid taxes. Underpaid tax deposit using electronic Deposit Letter with e-Billing system.